MHealth use for non-communicable diseases care in primary health: patients' perspective from rural settings and refugee camps. (11th October 2018) - Saleh, Shadi; Farah, Angie; El Arnaout, Nour; Dimassi, Hani; El Morr, Christo; Muntaner, Carles; Ammar, Walid; Hamadeh, Randa; Alameddine, Mohamad
Abstract: Background: Non-communicable diseases (NCDs) account for 85% of deaths in Lebanon and contribute to remarkable morbidity and mortality among refugees and underserved populations. This study assesses the perspectives of individuals with hypertension and/or diabetes in rural areas and Palestinian refugee camps towards a population based mHealth intervention called 'eSahha'. Methods: The study employs a mixed-methods design to evaluate the effectiveness of SMSs on self-reported perceptions of lifestyle modifications. Quantitative data was collected through phone surveys, and qualitative data through focus group discussions. Descriptive statistics and bivariate analysis were performed. Results: About 93.9% ( n = 1000) of respondents perceived the SMSs as useful and easy to read and understand. About 76.9% reported compliance with SMSs through daily behavioral modifications. Women ( P = 0.007), people aged ≥76 years ( P < 0.001), unemployed individuals ( P < 0.001), individuals who only read and write ( P < 0.001) or those who are illiterate ( P < 0.001) were significantly more likely to receive and not read the SMSs. Behavior change across settings was statistically significant ( P < 0.001). Conclusion: While SMS-based interventions targeting individuals with hypertension and/or diabetes were generally satisfactory among those living in rural areas and Palestinian refugee camps in Lebanon, a more tailored approach for older, illiterate and unemployed individuals is needed.